Mixed oleic acid stealth liposomes for anticancer drugs delivery / Vicit Rizal Eh Suk - Vicit Rizal , Eh Suk (2018)
Liposomal drug Nano carrier from phospholipids has been widely explored and proven to be the preferred formulation for liposomal chemotherapy despite their high cost. Fatty acids are the best alternative to the conventional phospholipids liposomes attributed to their amphiphilic structure, ease of preparation, economical, and easily available. However, the lack of interest among researchers in exploring fatty acid liposomes for chemotherapy could be due to their low encapsulation efficiency of active ingredients, unstable, high-clearance in the blood system, and potentially causing cell lysis. This study focused on using mixed monounsaturated C-18 fatty acid, soy lecithin, and erucic acid for liposomal anticancer Nano carrier in chemotherapy. Erucic acid, with 22 alkyl carbon chain, expected to enhance liposomes stability, reduce the size, and increase encapsulation efficiency of active ingredients. The incorporation of the strongly proven biocompatible stealth material from PEGylated lipid, 1,2-dioleoyl-sn-glycero-3-phosphoethanolamide-N-[methoxy (polyethylene glycol)-2000 (DOPEPEG2000) improved stability and prolong the lifetime of liposomes. The pH equilibrium curves for all lipids were obtained by titrating oleic acid, soy lecithin, or erucic acid against 0.05 mol dm-3 hydrochloric acid to define the region where liposomes were mostly presence. Liposomes were prepared by employing the thin lipid hydration technique followed by pH adjustment to produce the desired liposome regime. The thin layer of lipid was hydrated with saline phosphate buffered (PBS) at the concentration higher than their critical vesicle concentration (CVC). The optical polarizing microscope (OPM) displayed the presence of liposomes through their unique birefringence property while the micrograph high resolution-transmission electron microscope (HR-TEM) established that the liposomes had the circular silhouette with the size ranging from 100 to 600 nm. These findings were supported by the data obtained from the dynamic light scattering measurements with the lowest surface charge of mixed oleic acid-erucic acid liposomes around -90 mV. The encapsulation efficiency of different anticancer drugs namely folinic acid, doxorubicin, methotrexate, and irinotecan were above 60% while more than 20% of the anticancer drugs were released after 24 hours showing a slow released property which was very useful for inhibiting the proliferations of cancer cells. Fabrication of fatty acid liposomes may potentially be beneficial for manufacturing the novel biomimetic system for drug delivery vehicles.